A Review of Solar Tracker Control Strategies - Ali Basrah Pulungan; Lovely Son; Syafii Syafii (IAES Indonesia Section, 2018)
The efficiency of solar panels is an interesting study now, due to the limitation of material capabilities used in the manufacture of solar panels. The increasing of the received radiation intensity from the sun is a way to improve the performance of solar panels. In this paper will be exposed increased efficiency of solar panels using the method of tracking the sun. The commonly used sunlight tracking is an active tracker, due to significant efficiency improvements compared to passive trackers. The active tracker consists of a single axis and a double axis, both of which use a motor as a driver. This motor is controlled using a microcontroller or a programmable logic controller (PLC). Furthermore, the automatic tracker based on microcontroller or programmable logic controller (PLC) on single axis or double axis which is implemented and can be tested in real time or periodically.